PREPARATION FOR THE IMPLEMENTATION OF STATE POLICY IN THE FIELD OF VOLUNTEERING IN SOCIAL ACTIVITIES AND HIGHER EDUCATION - Khushnazarova Mamura Nodirovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the level of knowledge of bachelors in social work for the implementation of the state policy in the field of volunteering, the possibilities of solving the current important problems of the society are discussed